The role of force chains in granular materials: from statics to dynamics. Issue 7 (3rd August 2017) - Zhang, Lingran; Nguyen, Nho Gia Hien; Lambert, Stéphane; Nicot, François; Prunier, Florent; Djeran-Maigre, Irini
Abstract : This paper investigates the role of force chains in granular materials under both quasi-static biaxial loading and dynamic impact loading conditions. This study is mainly interested in investigating the role of force chains on the global mechanical responses of samples as well as on the microstructure of granular materials. For this purpose, discrete element methods are adopted to perform different loading tests. Granular materials are modelled as aggregations of poly-disperse spherical particles. Results first show that force chains are responsible for the strength of the sample: in 2D biaxial test, the establishment and buckling of force chains are responsible for the evolution in terms of deviatoric stress; in 3D dynamic impact test, the development and the buckling of force chains are responsible for the evolution of impact force on the impacting projectile. Second, force chains are found to play an important role in the microstructure of granular materials: in statics, the buckling of force chains mainly locates inside the shear band, and is related to the increase in local void around the buckling grain as well as the increase in kinetic energy inside the sample; in dynamic test, the number of buckled force chains is correlated with the energy dissipation inside the sample.